Students' Perspectives Concerning Intercultural Competence Development during their Academic Exchange Period - Ricardo Miguel André das Dores (Universidad Pedagógica Nacional, 2020)
In this case study with a qualitative approach we aim to analyze perspectives of students on the intercultural competence and its development during their academic exchange period abroad. The increasingly competitive and globalized labor market requires knowledgeable professionals from an intercultural point of view. The techniques to collect data were semi-structured interviews and participant observation. Data analysis procedures followed content analysis. The results suggest that the perception of cultural differences increases in students, although the development and improvement of institutional policies of universities is necessary for the preparation of strategies that promote the development of said competences. Conclusions point towards the increased relevance that intercultural competence represents on Higher Education nowadays and on future professionals.